2002
DOI: 10.14411/eje.2002.058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the arrival of Harmonia axyridis on adults of Coccinella septempunctata and Coleomegilla maculata (Coleoptera: Coccinellidae)

Abstract: Abstract. The impact of the arrival of the exotic coccinellid Harmonia axyridis on the biological control and dispersion of apple mites and aphids, and on the vertical distribution of the established coccinellids Coccinella septempunctata and Coleomegilla macu lata have been studied. Assemblages of adults of the three coccinellid species were tested on apple saplings and on apple trees against Aphis citricola and Tetranychus urticae. The presence or substitution of adults of H. axyridis for adults of C. macula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 29 publications
0
34
1
Order By: Relevance
“…Adults of C. maculata and C7 did not modify their vertical distributions on apple trees in response to the presence of H. axyridis adults (Lucas et al 2002). In laboratory tests with abundant prey, however, females of the Azorean indigenous ladybird C. undecimpunctata laid fewer eggs in the presence of a H. axyridis female (but not a conspecific female) than when alone, perhaps as the result of interference competition (Soares and Serpa 2007).…”
Section: Proposed Mechanismsmentioning
confidence: 85%
“…Adults of C. maculata and C7 did not modify their vertical distributions on apple trees in response to the presence of H. axyridis adults (Lucas et al 2002). In laboratory tests with abundant prey, however, females of the Azorean indigenous ladybird C. undecimpunctata laid fewer eggs in the presence of a H. axyridis female (but not a conspecific female) than when alone, perhaps as the result of interference competition (Soares and Serpa 2007).…”
Section: Proposed Mechanismsmentioning
confidence: 85%
“…Specimens were also released in Connecticut in 1985 during a study of the potential of H. axyridis to control Matsucoccus resinosae Bean and Godwin (Homoptera: Margarodidae) (McClure 1987). This species preys on more than 30 different aphid species and so was considered as a suitable candidate for efficient biological control against many pests including: aphids (see Lucas et al 2007a;Tedders and Schaefer 1994;Hodek and Honȇk 1996), Tetranychidae (Lucas et al 1997(Lucas et al , 2002, Psyllidae (Fye 1981;Michaud 2001Michaud , 2002Michaud , 2004, Coccoidea (McClure 1986), Chrysomelidae , Curculionidae (Kalaskar and Evans 2001;Stuart et al 2002) and Lepidoptera (Koch et al , 2005Musser and Shelton 2003a). Its large body size, high voracity and predation efficiency (Schanderl et al 1985;Osawa 2000;Soares et al 2001;Labrie et al 2006) as well as its good colonization efficiency (Osawa 2000; were considered good characteristics to provide successful biological control of many pests.…”
Section: Harmonia Axyridis: Where and When?mentioning
confidence: 99%
“…Probably not. H. axyridis is euryphagous, exploiting mites (Lucas et al 1997(Lucas et al , 2002, psyllids (Michaud 2001(Michaud , 2002(Michaud , 2004 and other insect species. Furthermore, in Canada for example, at the end of the autumn, when all indigenous species have reached their overwintering sites, numerous individuals of the beetle are found in agricultural fields.…”
Section: Azores the First Failure Of H Axyridis?mentioning
confidence: 99%
“…In contrast, C. septempunctata and H. axyridis have become very abundant and broadly distributed throughout the continent following their introductions to North America, and they appear to be negatively interacting with native ladybird species (LaMana and Miller, 1996;Brown and Miller, 1998;Colunga-Garcia and Gage, 1998;Lucas et al, 2002;Michaud, 2002;Brown, 2003;Nault and Kennedy, 2003;Evans, 2004;Snyder et al, 2004;Yasuda et al, 2004). Elliott et al (1996) reported population declines of A. bipunctata and C. transversoguttata richardsoni Brown in midwestern field crops following the establishment of C. septempunctata.…”
Section: Discussionmentioning
confidence: 99%